Diagnóstico de la situación actual y perspectivas al mercado internacional del café en el departamento de Cundinamarca (2022)
Research on the production and export of coffee in the department of Cundinamarca, given the importance of this product within the regional economy. Therefore, a situational and prospective analysis of the production and export of coffee from Cundinamarca to the United States was carried out. Based on the conditions and factors that could constitute an advantage over other regions of the country and generate opportunities for growers in the region.